Legal Certainty Of Guarantee Of Movable And Non-Movable Property In Oral Agreements To Lend Money - Thesia Elestika Simanjuntak; Hasim Purba; Aflah, Aflah (SEAN Institute, 2024)
Money lending agreements can be made either in writing or verbally, with or without collateral as a form of trust between the parties. Although Indonesian law recognizes the validity of oral agreements based on the principles of freedom of contract and consensualism, in practice it often raises legal problems, especially regarding the legal certainty of the collateral provided. The purpose of this study is to determine the validity of money lending agreements made verbally in the Indonesian legal system, what are the forms of unlawful acts in money lending agreements made verbally with movable and immovable objects as collateral according to civil law, how is the legal certainty of the position and legal protection of the recipient and provider of movable and immovable objects in oral money lending agreements reviewed from. The method used in this writing is the normative legal research method, namely a method that refers to legal norms carried out by means of literature studies, this research is descriptive in nature, and the data is analyzed qualitatively. The results of the study found that oral money lending agreements are still recognized as valid in the Indonesian legal system as long as they meet the requirements in Article 1320 of the Civil Code, even though they have weaknesses in terms of proof. In its implementation, unlawful acts can occur as regulated in Article 1365 of the Civil Code when one party commits a violation such as misuse of collateral or withholding collateral even though the debt has been paid off. However, based on Supreme Court Decision Number 198K/Pdt/2019, legal certainty is still given to the parties through the protection of their rights, as evidenced by a court decision ordering the return of collateral and excess payments to the entitled party, thus showing that even though the agreement was made verbally, the principles of justice and legal certainty are still upheld by the court.